The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-11375-x
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin, Twist and Snail: Transcriptional regulation of EMT in smokers and COPD, and relation to airflow obstruction

Abstract: COPD is characterised by poorly reversible airflow obstruction usually due to cigarette smoking. The transcription factor clusters of β-catenin/Snail1/Twist has been implicated in the process of epithelial mesenchymal transition (EMT), an intermediate between smoking and airway fibrosis, and indeed lung cancer. We have investigated expression of these transcription factors and their “cellular localization” in bronchoscopic airway biopsies from patients with COPD, and in smoking and non-smoking controls. An imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 58 publications
(61 reference statements)
0
76
0
Order By: Relevance
“…FAM13A has been reported to regulate the β-catenin signaling in airway epithelial cells [10,25], and we found that FAM13A negatively regulates β-catenin activity in endothelial cells as well. β-catenin signaling has been involved in epithelial-to-mesenchymal transition in pulmonary disease and cancer [8,12,26]. Also, β-catenin has been reported to promote EndMT through nuclear accumulation and subsequent activation of TCF/Lef transcription factors [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…FAM13A has been reported to regulate the β-catenin signaling in airway epithelial cells [10,25], and we found that FAM13A negatively regulates β-catenin activity in endothelial cells as well. β-catenin signaling has been involved in epithelial-to-mesenchymal transition in pulmonary disease and cancer [8,12,26]. Also, β-catenin has been reported to promote EndMT through nuclear accumulation and subsequent activation of TCF/Lef transcription factors [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It's well known that many signaling pathways are involved in EMT regulation, such as TGF-β [28], Wnt [29], Notch [30], TNF [31], and BMPs [32]. Several transcription factors also take part in the regulation of EMT, including the Snail/Slug family, Twist, and SIP1/ZEB2, function as molecular switches for the EMT program [33][34][35]. Recent studies have shown that dysregulated expression of lncRNAs in some cancers may regulate EMT and affect disease progression [36].…”
Section: Discussionmentioning
confidence: 99%
“…FAM13A has been reported to regulate the β-catenin signaling in airway epithelial cells [10, 25], and we found that FAM13A negatively regulates β-catenin activity in endothelial cell as well. β-catenin signaling has been involved in epithelial-to-mesenchymal transition in pulmonary disease and cancer [8,12,26]. Also, β-catenin has been reported to promote EndMT through nuclear accumulation and subsequent activation of TCF/Lef transcription factors [13, 14].…”
Section: Discussionmentioning
confidence: 99%